2017
DOI: 10.1159/000456666
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Ulcer Hemorrhage - a Potential Life-Threatening Complication of Intragastric Balloon Treatment of Obesity

Abstract: Background: Some morbidly obese patients do not qualify for bariatric surgery due to general health contraindications. Intragastric balloon treatment might be a therapeutic option in the above-mentioned cases. It can prime super-obese patients with end-stage disease for bariatric surgery. As a neoadjuvant therapy before surgery, it leads to a downstage of the disease by preliminary weight reduction, to an improvement in general health and, in summary, to a reduction of the perioperative risk. It is generally c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…One OD had a gastric ulcer hemorrhage caused by taking aspirin against medical advice. This led to premature IGB removal one month prior to the scheduled time . However, his metabolite ratios were within the range of other patients taking part in the study.…”
Section: Methodsmentioning
confidence: 93%
“…One OD had a gastric ulcer hemorrhage caused by taking aspirin against medical advice. This led to premature IGB removal one month prior to the scheduled time . However, his metabolite ratios were within the range of other patients taking part in the study.…”
Section: Methodsmentioning
confidence: 93%
“…IGB‐related AEs commonly include abdominal pain or discomfort usually epigastric, nausea, vomiting, halitosis, belching, flatulence, and psychological discomfort toward the presence of a foreign body 14. In one study, the most common side effects reported were nausea, abdominal pain, gastric erosion, and flatulence occurring 72%, 39%, 32%, and 24% of the time, respectively 15. Early retrieval of the IGB under conscious sedation or general anesthesia has resulted in aspiration pneumonia, perforation or mucosal tears within the esophagus, ulcers within the gastroesophageal junction, and pneumonitis 7,16,17.…”
Section: Discussionmentioning
confidence: 99%
“…14 In one study, the most common side effects reported were nausea, abdominal pain, gastric erosion, and flatulence occurring 72%, 39%, 32%, and 24% of the time, respectively. 15 Early retrieval of the IGB under conscious sedation or general anesthesia has resulted in aspiration pneumonia, perforation or mucosal tears within the esophagus, ulcers within the gastroesophageal junction, and pneumonitis. 7,16,17 Pancreatitis is an increasingly recognized complication of IGB insertion and generally occurs within 1-year post-IGB insertion.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Among OB, 1 patient had a gastric ulcer hemorrhage caused by taking aspirin against medical advice. This led to premature IGB removal 1 month before the scheduled time [19]. However, his RMR and RMR/mass were within the range of results of other patients taking part in the study, and he was not excluded from the study.…”
Section: Patientsmentioning
confidence: 99%